Telehealth Effectiveness in Pregnancy Service: Integrative Review - Lantiar winda oktari pondawati (Unnes Journal of Public Health, 2023)
Background: Physical distancing makes all health services, especially maternal and child health hampered. This forces health service providers to use remote technology or known as telehealth, telemedicine, and telemonitoring to monitor pregnant women. Telehealth is considered an effective method to reduce the spread of the COVID-19 virus. Method: Integrative review. Articles were searched using databases including Pubmed, Wiley Online Library, Sciencedirect, and Proquest. Assessment of the articles quality used the instrument tool from JBI (Joana Briggs Institute). Result: The ten articles obtained consisted of eight original research articles and two review articles. The results of this review showed seven indicators of the effectiveness of telehealth in pregnancy services, namely; 1) length of time used; 2) telehealth reuse; 3) services provided; 4) the technology used; 5) inspection plan compliance; 6) efficiency of time used by health workers; 7) patient satisfaction, and there are two unfound indicators, namely; 1) diagnostic accuracy and 2) closeness of patients to health workers. There are other indicators found regarding usage costs. Conclusion: Most articles stated that using telehealth is effective in prenatal care, but it cannot be used completely in pregnancy checks. Therefore, a face-to-face visit is still a must to find out more about the mother's condition.